PROMOSI PERSONAL SELLING SEBAGAI SALAH SATU USAHA MENDORONG PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN - Kurniasari, Rani (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2015)
Currently buyers already clever in choosing a product to be bought. Prospective buyers have a wide range of alternative options of similar products. For new products and has not been known to the public requires promotion in order to be better known. One of the promotional activities that can be done is the promotion of personal selling. With this promotion potential buyers can directly face to face with the marketing power of a product, so that prospective buyers can also learn more about the details of the product to be bought as well as the benefits and advantages of the products chosen. The purpose of this study was to determine the personal selling promotional activities in encouraging consumer behavior in making purchasing decisions. With the marketing power of personal selling promotional activities, the sales force can influence buying behavior and ultimately making purchasing decisions. The method used by the researchers is that the secondary data through literature and through the property sales activity of homes in Greater Jakarta in 2014. In 2014 the house in jabodtabek property sales tend to decline so developers do personal selling activities more intensively. One of them is holding an exhibition at the Mall property by placing a powerful sales force. With the sales force conducting a reliable personal selling so as to influence the behavior of consumers in making purchasing decisions. Thus very likely they will be to buy back in the future because it was already familiar with the products offered so as to increase sales in the next year. Keywords: Personal Selling, Consumer Behavior, Purchase Decision